IMPLEMENTASI PROGRAM ONE DAY SERVICE AKTA KEMATIAN - Adelia Puspita; Andi Mulyadi; M. Rijal Amirulloh (Universitas Djuanda Bogor, 2023)
The Sukabumi Regency Population and Civil Registration Office is a government agency responsible for managing population records. To streamline the process of obtaining death certificates, this office has introduced a flagship initiative known as the One Day Service program, comprising three sections: the Occupational Identity Section, the Migratory Section, and the Birth and Death Section. Under this program, applicants can complete their death certificate applications within a single day, provided they meet the necessary requirements. Despite the local government's endeavors to implement the One Day Service program, preliminary observations suggest that population administration services still require up to three days to complete. The researchers have presented their findings in a tabular format. This study employs qualitative research methods to evaluate the implementation of the One Day Service program for death certificates at the Sukabumi Regency Population and Civil Registration Office. Data collection techniques encompass interviews, observations, and document analysis. The analysis of the data is qualitative in nature. The results reveal that the execution of the One Day Service program falls short of optimal due to inadequate infrastructure support for the program.